2022
DOI: 10.3390/molecules27144437
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Method Development for 19 Alkyl Halides as Potential Genotoxic Impurities by Analytical Quality by Design

Abstract: Major issues in the pharmaceutical industry involve efficient risk management and control strategies of potential genotoxic impurities (PGIs). As a result, the development of an appropriate method to control these impurities is required. An optimally sensitive and simultaneous analytical method using gas chromatography with a mass spectrometry detector (GC–MS) was developed for 19 alkyl halides determined to be PGIs. These 19 alkyl halides were selected from 144 alkyl halides through an in silico study utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Implementing QbD in RP-HPLC techniques has demonstrated that it enhances analytical findings by increasing method performance measures like accuracy, precision, and robustness. [11][12][13][14]…”
Section: Qbd In Analytical Methodsmentioning
confidence: 99%
“…Implementing QbD in RP-HPLC techniques has demonstrated that it enhances analytical findings by increasing method performance measures like accuracy, precision, and robustness. [11][12][13][14]…”
Section: Qbd In Analytical Methodsmentioning
confidence: 99%
“…Currently, the detection methods for halogenated compounds largely focus on the trace-level analysis of relevant substances within active pharmaceutical ingredients (APIs) due to their potential genetic toxicity. These methods include the utilization of highly sensitive LC/GC–MS techniques as well as chemical derivatization to enhance the detection response of halogenated compounds. However, in the assay determination of halogenated compounds, conventional GC methods are inadequate due to the inherent instability of certain halogenated compounds and sometimes the lack of a stable and accessible method for obtaining analytical reference standards.…”
Section: Introductionmentioning
confidence: 99%
“…Most pharmaceutical companies utilize the guidelines provided by the European Medicines Agency and the ICH M7(R1) to regulate toxic impurities in drug substances (European Medicines Agency, 2006;ICH Harmonised Guideline, 2017). Following this, further research studies have been conducted to assess the carcinogenic and genotoxic contaminants found in pharmaceutical drug substances using a variety of analytical techniques including HPLC, ultra-performance liquid chromatography, GC, LC-tandem mass spectrometry, and GC-MS. (Babu et al, 2018;Balaji et al, 2022;Balaji & Sultana, 2017;Chen et al, 2020;Chittireddy et al, 2023;Feng et al, 2016;Gopalakrishnan & Devi, 2016;Grace et al, 2019;Kosuri et al, 2023;Lee et al, 2022;Louati et al, 2018;Narapereddy & Alladi, 2023;Nekkala et al, 2017;Neyer et al, 2020;Pandey et al, 2011;Sajan et al, 2015;Siva Jyothi & Venkatnarayana, 2021;Sojitra et al, 2019;Tatipamula et al, 2019;Uppala & Arthanareeswari, 2021;Vijaya Bhaskar Reddy et al, 2014;Wang et al, 2016;Yelampalli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%